Fourniers Gangrene: Approaches to the Diagnosis and Treatment - Ashrafuzzaman, Md; Bhattacharjee, Avisak; Rahman, Mahbubur (Delta Medical College Journal, 2017)
Background: Fourniers gangrene is a rare, rapidly progressive, necrotizing fasciitis of the external genitalia and perineum. Objective: The main aim of this study was to observe comprehensively the disease profile of Fourniers gangrene, with a specific intent to observe the proportion of patient presenting with Fourniers gangrene. Materials and method: This cross sectional study was done in Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh. By purposive sampling from the admitted patients of department of Surgery 22 patients were finalized according to the eligibility criteria. Patients were thoroughly evaluated and managed and all relevant data were recorded. Data were managed, edited and plotted in tabular and figure form. Data analysis was done by chi square test. p value was significant at <0.05. Results: The mean ±SD age of the patients was 43.9±14.82 years. Among the study subjects 68.2% showed insidious onset whereas remaining showed abrupt onset. Both cutaneous and anorectal factors claimed the highest (36.4%) of etiology. Pain and Oedema were the prime manifestation. In 59% cases testes were not exposed. In 36.4% cases only scrotum was involved whereas in 22.7% cases both scrotum and perineum were involved. After provision of aggressive treatment in 72.7% cases no complication was observed. During treatment 9.1% subjects expired. Conclusion: Elderly and low economic profile people are frequently affected with Fourniers gangrene. To reduce the significant morbidity and mortality aggressive medical and surgical management is mandatory. Delta Med Col J. Jul 2017 5(2): 68-75